Military-Historical Anthropology: Vectors of Theoretical Polemic in Russian and English Historiography - F. V. Nikolae; L. V. Sofronova; A. V. Khazina (Научный диалог)
A classification of theoretical approaches in military-historical anthropology is proposed. The authors note that social constructivism prevails in English-language historiography as a whole, while in Russian studies an existential approach does. It is shown that the socio-cultural direction and the phenomenology of the front-line experience have recently begun to play an increasing role. It is concluded that a theoretical analysis of the differences between these approaches allows not only to identify their strengths and problematic sides, but also to outline the prospects for interaction between them. The authors note that the most promising today is the setting for the participation of representatives of the academic community in joint cultural practices of representing the front-line experience with combatants, which makes it possible to make the dialogue between the phenomenology of front-line experience and the socio-cultural approach the most productive. It is argued that within the framework of such a dialogue, the question of the relationship between normative social structures and local practices should not be reduced to a previously known answer. It is emphasized that it makes sense not to level out or radically absolutize the theoretical tension between the indicated approaches, but to work it out — to look for points of practical interaction and modification of existing strategies for comprehending the past.